Non-invasive serum markers and transient elastography in staging advanced chronic hepatitis C - Buivydienė, Arida; Basytė, Viktorija; Valantinas, Jonas (Acta medica Lituanica, 2016)
Objectives. In the past decade researchers are presenting indirect non-invasive serum markers for liver fibrosis and cirrhosis evaluation. Our aim was to evaluate effectiveness in staging advanced liver disease when using transient elastography and nine non-invasive serum markers: APRI, FIB-4, ASPRI, LSPS, P2/MS, FibroQ, Fibro-α, Pohl, CDR. Methods. 162 patients with hepatitis C infection were included in this study. Patients were divided in two groups, regarding histopathologic results: advanced liver fibrosis and cirrhosis. The following laboratory measures were obtained in all patients: ALT, AST, albumin, total bilirubin, alkaline phosphatase, gamma glutamyl transferase, INR, hemoglobin, platelet count, alfa fetoprotein, segmented neutrophils count and percentage and monocytes percentage. Transient elastography and nine non-invasive serum markers – APRI, FIB-4, ASPRI, LSPS, P2/MS, FibroQ, Fibro-α, Pohl, CDR  –  were compared with the  results of the  histopathological examination. A statistical analysis was done using the Student t-test, the Spearman’s rank correlation and the area under receiver-operating characteristic curves (AUROCs). Results. All nine non-invasive markers correlated significantly with the liver fibrosis stage (P
Keywords: non-invasive serum markers; liver fibrosis; liver cirrhosis; transient elastography; hepatitis C